Variants of aminoacyl‐tRNA synthetase genes in Charcot‐Marie‐Tooth disease: A Korean cohort study. Issue 1 (1st December 2021) - Nam, Da Eun; Park, Jin Hee; Park, Cho Eun; Jung, Na Young; Nam, Soo Hyun; Kwon, Hye Mi; Kim, Hyun Su; Kim, Sang Beom; Son, Won Seok; Choi, Byung‐Ok; Chung, Ki Wha
Abstract: Charcot‐Marie‐Tooth disease (CMT) and related diseases are a genetically and clinically heterogeneous group of peripheral neuropathies. Particularly, mutations in several aminoacyl‐tRNA synthetase (ARS) genes have been reported to cause axonal CMT (CMT2) or distal hereditary motor neuropathy (dHMN). However, the common pathogenesis among CMT subtypes by different ARS gene defects is not well understood. This study was performed to investigate ARS gene mutations in a CMT cohort of 710 Korean families. Whole‐exome sequencing was applied to 710 CMT patients who were negative for PMP22 duplication. We identified 12 disease‐causing variants (from 13 families) in GARS1, AARS1, HARS1, WARS1, and YARS1 genes. Seven variants were determined to be novel. The frequency of overall ARS gene mutations was 1.22% among all independent patients diagnosed with CMT and 1.83% in patients negative for PMP22 duplication. WARS1 mutations have been reported to cause dHMN; however, in our patients with WARS1 variants, CMT was associated with sensory involvement. We analyzed genotype‐phenotype correlations and expanded the phenotypic spectrum of patients with CMT possessing ARS gene variants. We also characterized clinical phenotypes according to ARS genes. This study will be useful for performing exact molecular and clinical diagnoses and providing reference data for other population studies.